Ruthenium(II)-Catalyzed Regioselective Ortho Amidation of Imidazo Heterocycles with Isocyanates - Khullar, S.; Mandal, S.K. (American Chemical Society, 2016)
Direct ortho amidation at the phenyl ring of 2-phenylimidazo heterocycles with aryl isocyanates has been achieved via a chelation-assisted cationic ruthenium(II) complex catalyzed mechanism. The methodology provides a straightforward, high-yielding regioselective approach toward the synthesis of an array of ortho-amidated phenylimidazo heterocycles without prior activation of C(sp2)–H. This also reports the first method for coupling of aryl isocyanates with the imidazo[1,2-a]pyridine system via a pentacyclometalated intermediate. The methodology is found to be easily scalable and could be applied toward the selective ortho amidation of 2-heteroarylimidazo[1,2-a]pyridine frameworks.
Only IISERM authors are available in the record.
Keywords: Heterocycles; 2-phenylimidazo; Amidation